2015
DOI: 10.5194/tc-9-151-2015
|View full text |Cite
|
Sign up to set email alerts
|

Observing Muostakh disappear: permafrost thaw subsidence and erosion of a ground-ice-rich island in response to arctic summer warming and sea ice reduction

Abstract: Abstract.Observations of coastline retreat using contemporary very high resolution satellite and historical aerial imagery were compared to measurements of open water fraction, summer air temperature, and wind. We analysed seasonal and interannual variations of thawing-induced cliff top retreat (thermo-denudation) and marine abrasion (thermoabrasion) on Muostakh Island in the southern central Laptev Sea. Geomorphometric analysis revealed that total ground ice content on Muostakh is made up of equal amounts of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
190
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(198 citation statements)
references
References 79 publications
7
190
1
Order By: Relevance
“…Much of the Chukchi and Beaufort seas' coastlines are similarly ice-rich and can be expected to be subject to the same mechanisms of geomorphologic change in response to shifts in environmental drivers of coastal dynamics (Ping et al, 2011). Regionally, relevant shifts in the energy and water balances at the land-atmosphere interface (Boike et al, 2013), increases in Lena River discharge (Fedorova et al, 2015) and increases in the duration of open water and coastal erosion (Günther et al, 2015) have recently been observed, matching similar circumpolar observations (Barnhart et al, 2014).…”
Section: Study Areasupporting
confidence: 58%
See 3 more Smart Citations
“…Much of the Chukchi and Beaufort seas' coastlines are similarly ice-rich and can be expected to be subject to the same mechanisms of geomorphologic change in response to shifts in environmental drivers of coastal dynamics (Ping et al, 2011). Regionally, relevant shifts in the energy and water balances at the land-atmosphere interface (Boike et al, 2013), increases in Lena River discharge (Fedorova et al, 2015) and increases in the duration of open water and coastal erosion (Günther et al, 2015) have recently been observed, matching similar circumpolar observations (Barnhart et al, 2014).…”
Section: Study Areasupporting
confidence: 58%
“…Ships leaving Tiksi, one of the major ports on the Northeast Passage, travel within sight of Muostakh Island, and it has therefore long been an object of research, from as early as the late nineteenth century. This research includes studies of coastal dynamics, and coastline erosion rates observed at Muostakh Island in the central Laptev Sea include some of the highest observed in the Arctic (Grigoriev et al, 2009 Günther et al, 2015), polygenetic in origin and characterized at the ground surface by the polygonal network of ice wedges formed over thousands of years by meltwater infiltration into cold winter thermal contraction cracks (Schirrmeister et al, 2011b). Coastal thermo-erosion on Muostakh Island varies widely in intensity (from close to 0 to over 25 m a −1 ) over a relatively small region (Grigoriev et al, 2009;Günther et al, 2015).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The permanently frozen ground extends below sea level on the shallow Arctic shelves as submarine permafrost. There is evidence in northern Alaska and the Laptev Sea area for recent acceleration in the rate of coastal erosion (e.g., Günther et al, 2015) related in parts to more open water and higher wave energy due to reduced sea-ice coverage, rising sea level, and more rapid thermal abrasion along coasts with high volumes of ground ice. Nearshore zones are transient zones for terrigenous matter, which arrives via coastal erosion, river discharge, and sea ice (e.g., Forbes, 2011).…”
Section: Linked Through Permafrost: Land-ocean Interactions In the Armentioning
confidence: 99%